A qualitative exploration of how oral trials are used in dysphagia management in one inpatient hospital. Issue 2 (29th January 2022) - Julier, Rebecca; Benfield, Jacqueline K.
Abstract: Background: The lack of high‐quality evidence to support specific treatment approaches has been widely documented in the existing literature, with evidence suggesting speech and language therapists (SLTs) frequently rely on experience and expert opinion to inform treatment. One approach that is commonly used within dysphagia management, in spite of a lack of existing evidence to support its efficacy, is the use of oral trials, otherwise known as swallow trials or tasters. This approach involves offering specified, limited amounts of oral diet or fluids for those at risk of aspiration or choking if full amounts are taken orally and may be recommended for rehabilitation or quality of life. Methods & Procedures: A total of nine SLTs working in one acute hospital volunteered to participate in focus groups in order to discuss their experience and clinical reasoning for using oral trials within one inpatient hospital setting in the UK. The objectives of this study were (1) to explore how oral trials are used within one inpatient hospital; (2) to consider the barriers and facilitators to the approach; and (3) to consider why this approach may be favoured over other evidenced dysphagia therapies. A grounded theory approach was used to guide data analysis, using two independent coders to identify themes within the focus groups. Outcomes & Results: Analysis of data revealed the following themes: (1) delivering oral trials requires 'a whole team approach'; (2) SLTs vary recommendations based on patient and environmental factors; and (3) oral trials as a holistic approach. Conclusions & Implications: The use of oral trials was considered by SLTs to be a holistic and flexible approach which can be adapted to a range of patient and environmental factors. Although clinical experience guided rationale, an understanding of the principles of neuroplasticity and swallow physiology was also integral to the approach. Further research is warranted to investigate the use and efficacy of oral trials across the SLT community and within specific patient groups and different environments.